Exploring and modeling the reading-writing connection in EFL integrated writing - Ye, Wei; Liu, Jianda (Frontiers in Psychology, 2023)
Reading-to-write tasks have increasingly been used in high-stakes language tests worldwide; however, the nature of the reading-writing connection is not well understood. This study utilized a mixed-methods approach to ground descriptions of EFL cognitive processes and identify process interaction patterns to determine how reading and writing were connected. Grounded theory analysis of fourteen EFL learners' writing think-aloud protocols showed that students engaged in an interactive composing process involving source reading, comprehension monitoring, planning, language monitoring, narration monitoring, and continuity evaluation. We also conducted a confirmatory factor model study on 486 EFL learners' responses to a self-developed writing questionnaire, which covered five factors, including reading monitoring, narration monitoring, ideational planning, continuity evaluation, and skill integration. The findings showed that reading monitoring was the only factor that had a direct and significant impact on skill integration, a composite factor covering discourse synthesizing and source using processes. Based on the discussion of the theoretical, empirical, and pedagogical implications of the current findings, we called for more studies to explore the use of three pillar skills–reading, writing, and language use–to support EFL integrated writing. We also suggested that test designers include explicit rating descriptor(s) for source using to evaluate reading comprehension, and instructors enhance reading instruction to improve task performance.